Research on the operational properties of the soft gripper pads - Marcin Białek; Dominik Rybarczyk (Scientific Reports)
Abstract Grippers are commonly used as a technological tooling for manipulators. They enable robots to interact with objects in their work area. Grippers have a wide range of differentiation focused on the operation performed and the properties (e.g. shape) of the object being gripped. Their design and functionality are constantly being modified, tuned and developed by both academic and industrial units. Consequently, this paper presents a proposal for a lightweight jaw using MR fluid, which can be implemented in a jaw gripper (e.g. Robotiq 2F-140) to form a hybrid soft-rigid structure. In addition, methods are presented for studying the use of soft structures in a jaw gripper. As part of the work carried out, a model of the cushion and jaw of the gripper was developed, the FEM was used to obtain the character of the deformation when the object is axially plunged into it. Experimental plunging tests as well as dynamic tests of object transfer were also carried out. The work carried out allowed to demonstrate several key aspects of the grippers area. The soft structures of the grippers should be studied in terms of the force required to deform them. This determines their applicability to fragile and deformable objects. Dynamic measurements of the handling of objects of different shapes, with simultaneous measurement of force, allow the effectiveness of the use of soft structures in the gripper to be determined. Such experiments will make it possible to determine the measurable stability and repeatability of the grasp. The results of the research and experiments will be particularly applicable to robotic arms with relatively low lifting capacity.